2020
DOI: 10.3389/fbioe.2020.575442
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutrition in the Prevention and Intervention of Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is a rapidly growing epidemic, which leads to increased mortality rates and health care costs. Nutrients (namely, carbohydrates, fat, protein, mineral substances, and vitamin), sensing, and management are central to metabolic homeostasis, therefore presenting a leading factor contributing to T2D. Understanding the comprehensive effects and the underlying mechanisms of nutrition in regulating glucose metabolism and the interactions of diet with genetics, epigenetics, and gut microbiota is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 134 publications
1
21
0
2
Order By: Relevance
“…Based on the literature, it is inconclusive whether the -308G/A polymorphisms in the TNF-α promoter results in T2DM susceptibility [22][23][24][25][26]. However, our findings follow recent meta-analysis studies [27,28], suggesting that TNF-α -308G/A can be considered as a risk factor for T2DM.…”
Section: Discussionsupporting
confidence: 58%
“…Based on the literature, it is inconclusive whether the -308G/A polymorphisms in the TNF-α promoter results in T2DM susceptibility [22][23][24][25][26]. However, our findings follow recent meta-analysis studies [27,28], suggesting that TNF-α -308G/A can be considered as a risk factor for T2DM.…”
Section: Discussionsupporting
confidence: 58%
“…Adhering to the recommended amounts of macro and micronutrients of carbohydrates, fat, protein, vitamins, and minerals form part of the underlying mechanisms needed to regulate glucose metabolism to manage diabetes effectively [88], whether alone or in combination with drug therapy. Studies have shown a positive association between diets high in sugar and the development of T2DM [89], and an increase in the risk of insulin resistance and T2DM was found in people with high intakes of red meat, sweets, and fried food [90].…”
Section: Dietmentioning
confidence: 99%
“…Avances recientes enfocados en la nutrición de precisión han descubierto que la dieta de los individuos puede incrementar el riesgo de desarrollar DM2 al interactuar con variantes genéticas específicas, modificando a su vez las características epigenéticas y la expresión de genes con la subsecuente alteración de las vías metabólicas 36 . Por ejemplo, se ha observado en ratas que una dieta baja en proteína durante el embarazo puede disminuir la acetilación de la histona H3 del promotor de NR1H3, lo cual silencia su expresión e incrementa el riesgo de DM2 en el producto 37 .…”
Section: La Epigenética En La Prevención El Diagnóstico Y El Tratamientounclassified
“…Uno de los puntos más importantes que destacar es que, así como la dieta de los individuos puede incrementar el riesgo para desarrollar DM2 al interactuar la genética y la epigenética, de igual forma la epigenética lo puede disminuir al ser reversible. Las intervenciones dietarias son capaces de modificar la expresión y las modificaciones epigenéticas de los genes involucrados en las rutas metabólicas, mientras que los perfiles de expresión y los marcadores epigenéticos pueden funcionar como predictores de respuestas personalizadas 36 .…”
Section: La Epigenética En La Prevención El Diagnóstico Y El Tratamientounclassified